THE USE OF EDUCATIONAL TECHNOLOGY TO SUPPORT DIFFERENTIATED INSTRUCTION IN PRIMARY SCHOOL CLASSROOMS IN INDONESIA - Ulvah Sari Rezeki; Gemala Widiyarti (Sensei International Journal of Education and Linguistic, 2023)
Differentiated instruction is increasingly needed in primary schools because students enter classrooms with diverse readiness levels, learning interests, learning profiles, digital familiarity, and academic needs. However, many teachers still experience difficulty implementing differentiation because of limited time, large class size, assessment demands, and the complexity of providing varied learning pathways. Educational technology offers practical support for differentiated instruction by enabling diagnostic assessment, flexible grouping, multimodal content delivery, adaptive tasks, formative feedback, and student-paced learning. This study aims to examine how educational technology supports differentiated instruction in primary schools and how it affects students’ learning engagement and academic achievement. The study employed a mixed-method design using a quasi-experimental pretest-posttest control group approach supported by classroom observations, teacher interviews, student interviews, and document analysis. The participants were 124 Grade V students and eight primary school teachers. The experimental group received technology-supported differentiated instruction for eight weeks, while the control group received conventional instruction. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, and effect size analysis. Qualitative data were analyzed thematically. The findings showed that technology-supported differentiated instruction improved students’ achievement and engagement more substantially than conventional instruction. Qualitative findings revealed that educational technology helped teachers identify students’ needs, provide tiered materials, monitor learning progress, and give timely feedback. The study concludes that educational technology can strengthen differentiated instruction when it is pedagogically guided, assessment-informed, inclusive, and aligned with primary students’ developmental characteristics.